Meningkatkan Peran Masjid dalam Ibadah dan Pendidikan Islam: Studi Kasus di Masjid Namira Lamongan - Dwi Syamsih (Maneggio, 2024)
This research aims to illustrate the Islamic worship and education strategies implemented by the administrators of Namira Mosque. The paper discusses three main topics: mosque management, the enhancement of mosque administrators' roles, and factors that hinder or support program implementation. This qualitative study adopts a case study approach, employing observation, interviews, and documentation as data collection methods. Data validity is ensured through triangulation of methods and sources. The findings of the study indicate that: firstly, Namira Mosque effectively manages its operations, encompassing planning, organizing, implementing, and controlling functions; secondly, administrators of Namira Mosque optimize their roles by offering diverse activities and ensuring sufficient infrastructure to enhance worshipper experience; thirdly, supportive factors for role optimization and mosque functionality include well-equipped facilities, funding from the mosque's owner institution, and the dedication and loyalty of mosque administrators. Inhibiting factors are minimal, with inconsistent worshipper motivation being the primary challenge due to their personal commitments.